The Role of Government, Private Sector, and Community in Mangrove Conservation - Bheni David Dwiana; Achmad Husen; Dian Alfia Purwandari; Luthfi Jusniar Dwiputri; Zahra Nabilla (Jurnal Syntax Admiration, 2025)
Mangrove conservation plays a vital role in maintaining the balance of coastal ecosystems and mitigating climate change impacts. However, efforts to preserve these ecosystems are often impeded by land conversion, environmental degradation, and lack of coordination among the stakeholders involved. This article examines the application of multi-actor governance in mangrove conservation, focusing on the roles of government, the private sector, and local communities. This study employs a qualitative approach with thematic analysis, involving in-depth interviews and focus group discussions (FGDs) in several coastal areas of Indonesia that harbor significant mangrove ecosystems. The findings indicate that the government plays a key role in establishing policies and regulations; however, limited inter-institutional coordination remains a significant challenge. The private sector participates through corporate social responsibility (CSR) initiatives and sustainable partnerships, but their engagement is still suboptimal due to insufficient incentives and weak supportive policies. Local communities, particularly those residing adjacent to mangrove forests, play a crucial role in conservation despite ongoing tensions between short-term economic demands and long-term conservation objectives. Enhanced communication platforms and clearly defined incentives can facilitate more effective collaboration among these three actors, thereby strengthening sustainable mangrove conservation efforts. This article concludes that inclusive and coordinated multi-actor governance holds substantial potential to generate sustainable social, economic, and environmental outcomes for mangrove ecosystems and coastal communities.